Optimization of the Regulatory Framework to Attract Tertiary Sector Investment: A Policy Analysis in Garut Regency - Widaningsih, Widaningsih; Adiawaty, Susi; Mawardy, Vivy; Lokman, Asmidar (Pencerah, 2024)
The increase in investment in the tertiary sector, such as tourism, trade, and services, has become one of the strategic priorities of Garut Regency in driving regional economic growth. However, regulatory barriers, lack of legal certainty, and infrastructure challenges often pose major obstacles for investors. This study aims to analyze the existing regulatory framework, identify challenges in policy implementation, and offer recommendations for optimizing policies to attract more investment in the tertiary sector. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews with 15 informants, including officials from the Investment and Integrated Licensing Service Office (DPMPT), local business actors, prospective investors, and academics. Data analysis was conducted using triangulation methods, which included policy document analysis, investment statistics, and insights from interviews. The results of the study show that despite Garut Regency's great potential in the tertiary sector, such as natural tourism and trade, investment policy implementation is still suboptimal. Major inhibiting factors include the complexity of licensing procedures, lack of synchronization between regional and national policies, and insufficient structured investment promotion. The study recommends streamlining regulations, digitalizing the licensing system, and strengthening coordination between local governments and stakeholders. The conclusion of this study emphasizes the importance of optimizing an adaptive regulatory framework that aligns with investor needs. With more flexible and conducive policies, Garut Regency has the potential to become a leading destination for tertiary sector investment in Indonesia.